The Relationship of Grammatical Knowledge and Sentence Structure Knowledge with Cloze Test Based Reading Comprehension - Dhadhodara, Nitinkumar; Joshi, Bharat (Voices of Teachers and Teacher Educators, 2020)
The present study attempts to examine the relationship of grammatical knowledge and sentence structure knowledge with reading comprehension of higher education students. The main purpose of this paper is two-fold: first, to explore the reading comprehension of higher education students in the context of their grammatical knowledge level and sentence structure knowledge level; second, to examine correlation of grammatical knowledge and sentence structure knowledge with reading comprehension. The sample consisted of 54 students, who were studying in B.Ed. programme. The study was carried out by administering grammatical knowledge test, sentence structure knowledge test and cloze test. Descriptive analysis, one way ANOVA and pearson ‘r’ were employed to analyze the data. The study revealed that most of students had moderate level of grammatical knowledge, sentence structure knowledge and reading comprehension. There was significant difference found between the scores for reading comprehension in the context of their levels of grammatical knowledge and in the context of their levels of sentence structure knowledge also. The correlations between grammatical knowledge and sentence structure knowledge with reading comprehension were significant and positive.